Novel Cu4 and Cu4Cd6 clusters derived from flexible aminoalcohols: synthesis, characterization, crystal structures, and evaluation of anticancer properties. Issue 34 (10th August 2021) - Iman, Khushboo; Raza, Md Kausar; Ansari, Mursaleem; Monika,; Ansari, Azaj; Ahmad, Musheer; Ahamad, M. Naqi; Qasem, Khalil M. A.; Hussain, Sameer; Akhtar, Muhammad Nadeem; Shahid, M.
Abstract : The effect of a heterometal on a Cu(ii ) cluster has been exercised and observed to enhance anticancer activity and apoptosis. Abstract : Two new copper clusters, Cu4 and Cu4 Cd6 , with polydentate aminoalcohol ligands, diethanol propanolamine (H3 L 1 ) and bis–tris{2-[bis(2-hydroxyethyl)amino]-2-(hydroxymethyl)propane-1, 3-diol} (H6 L 2 ), have been synthesized under mild conditions and characterized thoroughly by single-crystal X-ray diffraction (XRD), infrared spectroscopy, elemental analysis, powder XRD, magnetic and DFT studies, and absorption and fluorescence spectroscopy. The cluster Cu4 exhibits a rare tetranuclear copper cubane core whereas Cu4 Cd6 forms an unusual heterometallic cage owing to the introduction of the second metal Cd into the ligand. A hexapodal ligand (H6 L 2 ) with N and O donor atoms was chosen deliberately for the construction of a high-nuclearity cluster, i.e., Cu4 Cd6 . Interestingly, both the clusters displayed significant cytotoxicity towards human cervical (HeLa) and lung (A549) cancer cells as evident from the shallow IC50 values [15.6 ± 0.8 μM (HeLa), 18.5 ± 1.9 μM (A549) for Cu4 , and 11.1 ± 1.5 μM (HeLa), 10.2 ± 1.3 μM (A549) for Cu4 Cd6 ] obtained after a 24 h incubation. However, moderate toxicity was observed toward immortalized lung epithelial normal cells (HPL1D) with IC50 values of 32.4 ± 1.2 μM for Cu4 and 27.6 ± 1.7 μM for Cu4 Cd6 . A cellular apoptotic study using HeLa cells revealed that the Cu4 cluster triggered apoptosis at both the early and late phases while the Cu4 Cd6 cluster facilitate apoptosis mainly at the late apoptotic stage. A standard 2′, 7′-dichlorodihydrofluorescein-diacetate (DCFH-DA) test affirms that both the clusters enhanced ROS production inside the cancer cells, responsible for promoting cell apoptosis. The decanuclear Cu4 Cd6 clusters demonstrated better anticancer activity compared to the tetranuclear Cu4 clusters, indicating the role of high nuclearity and additional Cd metal in the enhanced intracellular production of ROS.